Hepatitis C Virus‐Associated Aortitis Caused by Type I Cryoglobulins. Issue 1 (2017) - Lenhart, Adrienne; Meighani, Alireza; Hassan, Mona; Gordon, Stuart
ABSTRACT : N/A: Chronic hepatitis C virus infection (HCV) can present with cryoglobulinemic vasculitis, which is primarily associated with type II/III cryoglobulins. Type I cryoglobulins are usually seen in lymphoproliferative disease, and large vessel involvement with this type of vasculitis is rare. A 70‐year‐old man with chronic HCV presented with abdominal pain, leukocytosis, and rash. Computed tomography angiography showed thickening of the abdominal aorta consistent with large‐vessel vasculitis. He was found to have type I cryoglobulinemia and was treated with corticosteroids and ledipasvir/sofosbuvir with rapid resolution of his aortitis. This case emphasizes the need to recognize HCV as a potential etiology of large‐vessel vasculitis.